2014
DOI: 10.1111/codi.12582
|View full text |Cite
|
Sign up to set email alerts
|

Management of large bowel obstruction with self‐expanding metal stents. A multicentre retrospective study of factors determining outcome

Abstract: Experienced operators using a TTS technique achieved a better outcome for the emergency management of large bowel obstruction. Older, sicker patients and those with extracolonic and benign strictures fared less well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 28 publications
3
45
0
1
Order By: Relevance
“…15 As with all technical procedures, there is a learning curve for colonic SEMS placement. Retrospective series 22,28 and noncomparative studies 29,30 have shown that stent outcome is affected by operator experience. Technical success rate (and use of fewer stents) significantly improves after 20 procedures.…”
Section: 27mentioning
confidence: 99%
“…15 As with all technical procedures, there is a learning curve for colonic SEMS placement. Retrospective series 22,28 and noncomparative studies 29,30 have shown that stent outcome is affected by operator experience. Technical success rate (and use of fewer stents) significantly improves after 20 procedures.…”
Section: 27mentioning
confidence: 99%
“…Perforation rate ranged from 0 to 83%; the overall risk of perforation was about 5%, which is a relatively low risk, but the mortality rate of patients with perforations was 16% [28] . CS technical and clinical success are dependent on Endoscopist's experience: Geraghty reported that technical success and good outcome for the emergency management of ALBO by SEMS insertion did not vary by indication or site of obstruction but it is higher for experienced operators who had performed more than 10 procedures, using the through-the-scope (TTS) endoscopy technique [29] . Giannotti evaluating prospectively short and long term results from CS concluded that the interpretation of CS benefits may be ascribed to the experience of the endoscopist and the relatively low rate of complete colonic obstructions [30] .…”
Section: Risk Of Perforation After Sems Insertionmentioning
confidence: 99%
“…The application of SEMS has recently become more frequent for the palliation of metastatic colorectal cancer and as a bridge to surgery for obstructing tumors, despite the concerns regarding safety and efficacy in recent systematic reviews and meta-analyses (6,7). Additional considerable variations in practice may exist due to the lack of expertise and technical difficulties (8,9). …”
Section: Introductionmentioning
confidence: 99%
“…The wire is manipulated with either fluoroscopy alone, as in the over-the-wire (OTW) method, or combined with endoscopic visualization, as in the through-the-scope (TTS) technique (8,10). In the literature, it appears that experienced operators using TTS achieved better technical and clinical outcomes (8,9,11,12). The present study demonstrated that TTS is a practical tool for effectively resolving bowel obstruction in our unit.…”
Section: Introductionmentioning
confidence: 99%